Effect of Drying Conditions on Antioxidant Properties of Rosehip Fruits (Rosa canina sp.) - Koca, Ilkay; Sule Ustun, Nebahat; Koyuncu, Turhan (Asian Journal of Chemistry, 2010)
The objective of this work was to investigate the influence of drying conditions on antioxidants contents and antioxidant activity of rosehips. Freshly harvested rosehips were dried under 3 air temperatures (50, 60 and 70 ºC) at air flow rates of 0.5, 1.0 and 1.5 m s-1. The retention of total phenolics was best at 50 ºC and 1.5 m s-1 air flow rate. For the retention of total carotenoids and antioxidant activity, the appropriate drying conditions were found to be 70 ºC and 1.5 m s-1 air flow rate. For the highest retention of ascorbic acid, 60 ºC drying temperature and 1.5 m s-1 air flow rate was determined to be appropriate.